Case Report: ALPPS hepatectomy, an alternative to liver transplantation in central PRETEXT III hepatoblastomas: a case series - Garcia Moreno, Isabel Cristina; Alzate-Ricaurte, Sergio; Alzate Gallego, Edgar Dario; Hincapie-Ayala, Daniela; Serrano Ardila, Oscar Javier; Villegas Otalora, Jorge Ivan (Frontiers in Pediatrics, 2024)
INTRODUCTION: Hepatoblastoma is the most common malignant primary liver tumor in the pediatric population, accounting for 67% of cases in the United States. Surgical resection is the only curative treatment option; however, it can be performed in only 10% of patients with primary tumors. The two most common limitations for resection are the need for extensive resections and tumors in central locations. The therapeutic hypertrophy of healthy tissue achieved with ALPPS (Associating Liver Partition and Portal vein ligation for Staged Hepatectomy) enables larger resections and has been successfully employed in the pediatric population in recent years. OBJECTIVE: To present three cases of patients with centrally located PRETEXT II or III hepatoblastomas who underwent ALPPS procedure as a viable therapeutic alternative to liver transplantation. DISCUSSION AND RESULTS: Central PRETEXT III hepatoblastomas are typically indications for liver transplantation. Transplantation offers high five-year survival rates (73%). However, the associated morbidity, healthcare system costs, and limited availability make it necessary to explore alternative options. Series have reported the successful application of the ALPPS procedure in PRETEXT II and PRETEXT III hepatoblastomas in other locations. Therapeutically induced hypertrophy, characterized by an increase in the volume of healthy tissue in unaffected lobes or segments, enabled the resection of previously deemed unresectable lesions. The patients experienced uncomplicated postoperative courses and expected reduction in tumor markers. Chemotherapy selection followed the guidelines outlined in Block C of the SIOPEL IV protocol. CONCLUSIONS: ALPPS hepatectomy is a viable therapeutic option for patients with centrally located PRETEXT II or III hepatoblastomas.